The Role of Team and Individual Sports Co-Curricular Internship Programs on Academic Achievement in The Need For Professional Manpower - Narwikant Indroasyoko; Ruminto Subekti; Achmad Muhammad (Kodepena Indonesia, 2024)
Abstract This research aims to describe the factual and conceptual involvement between sports co-curricular programs and internships to meet the needs of professional workers in industry. Co-curricular sports participation during internships plays an important role in supporting efforts to meet the needs of professional workers in industry. Student involvement in co-curricular sports activities during an internship can help develop skills, knowledge and attitudes. This research uses a qualitative research method with a questionnaire as a data collection tool. The results of the research show that participation in co-curricular sports in internships provides opportunities for students to develop communication, leadership, teamwork and discipline skills. Apart from that, this experience also makes them understand the importance of health and fitness in the workplace, so that they can support the needs of a professional workforce in industries that require healthy and productive employees. Participating in co-curricular sports at the internship site makes a positive contribution in preparing students to enter the world of work. Therefore, educators and policy makers need to pay attention to and support the development of effective sports co-curricular programs as an integral part of formal education to create a more prepared and professional workforce in the future.